Molecular detection of begomoviruses associated with a new yellow leaf crumple disease of cucumber in Maharashtra, India - and M.B. SHIVANNA, L.M. SURESH, V.G. MALATHI (Indian Phytopathology, 2013)
During a survey conducted in 2008-10 on diseases of cucumber, an important salad crop, in three districts in Maharashtra state, India, severe yellowing and crumpling symptoms were observed in farmer’s field. The association of begomoviruses with this new disease designated as yellow leaf crumple disease of cucumber was investigated. Whitefly transmission and PCR amplification with begomoviruses specific replication initiator protein gene and coat protein gene clearly indicated the association of begomoviruses. On the basis of the sequence analysis of PCR amplicons obtained with Roja’s and core CP primers, the disease was found to be associated with five closely related begomovirus species. Three viruses identified in majority of the tested samples were, Tomato leaf curl New Delhi virus (ToLCNDV), Croton yellow vein mosaic virus (CYVMV) and Tomato leaf curl Karnataka virus (ToLCKaV). However, our study revealed the presence of two more viruses on cucumbers in less frequency, restricted only to one or two surveyed villages. These two identified begomoviruses showed highest identity (96 – 97%) in coat protein region with Tomato severe leaf curl virus (ToSLCV) and Pepper golden mosaic virus (PepGMV). Occurrence of more than one begomovirus in mixed infection was noticed in eleven samples, which indicates possibility of genetic reassortment, recombination and emergence of new strains of begomoviruses.